2011
DOI: 10.1080/01690965.2010.496553
|View full text |Cite
|
Sign up to set email alerts
|

How do roots and suffixes influence reading of pseudowords: A study of young Italian readers with and without dyslexia

Abstract: The study explored the different influences of roots and suffixes in reading aloud morphemic pseudowords (e.g., vetr-ezza, ''glass-ness''). Previous work on adults showed a facilitating effect of both roots and suffixes on naming times. In the present study, pseudoword stimuli including roots and suffixes in different combinations were administered to sixth-grade children with dyslexia (N022) and skilled readers (N044), matched for chronological age. Indeed, the sequential reading strategy of less proficient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 39 publications
(57 reference statements)
8
68
1
Order By: Relevance
“…The pattern of results in the L1 beginning readers approached previous studies suggesting that decomposition of complex words (or even multi-morphemic non-words) into morphemic units supports reading ability in younger readers (Burani et al, 2008;Marcolini et al, 2011;Traficante et al, 2011). According to the above-mentioned literature, morpheme-based reading might allow children to read units smaller than the whole word, but bigger than the grapheme or the syllable (see, for instance, Angelelli et al, 2014).…”
Section: Discussionsupporting
confidence: 64%
“…The pattern of results in the L1 beginning readers approached previous studies suggesting that decomposition of complex words (or even multi-morphemic non-words) into morphemic units supports reading ability in younger readers (Burani et al, 2008;Marcolini et al, 2011;Traficante et al, 2011). According to the above-mentioned literature, morpheme-based reading might allow children to read units smaller than the whole word, but bigger than the grapheme or the syllable (see, for instance, Angelelli et al, 2014).…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, there is evidence of morpheme-based reading in Italian students with dyslexia (Burani et al, 2008;Marcolini et al, 2011;Traficante et al, 2011), but no indications are present for the spelling process. In Italian, the regularity of the grapheme-to-phoneme and phoneme-to-grapheme mappings is in principle sufficient to process correctly most words; thus, morphological units may not be necessary for reading and spelling accuracy.…”
Section: Discussionmentioning
confidence: 93%
“…A series of studies demonstrated that morpheme-based reading is effective in secondary-school Italian readers with dyslexia (Burani, Marcolini, De Luca, & Zoccolotti, 2008;Traficante et al, 2011). These students read aloud pseudowords made up of a root and a derivational suffix (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of “compensated” dyslexic university students – where “compensated” is defined as those achieving higher than expected literacy in light of phonological deficits – showed that students’ strengths in morphological awareness were associated with improved reading outcome [37]. Other studies have similarly found that children with RD can rely on morphological structure to decode words faster, despite decoding difficulties [38,39]. Vocabulary skills have also been implicated as a compensatory mechanism for college students with RD [40], and have been shown to mediate between impaired verbal working memory and oral reading fluency in adolescents with RD [41].…”
Section: Cognitive Resiliencementioning
confidence: 99%